Implementación de un banco de pruebas para la visualización de los valores nominales de las magnitudes eléctricas propias de un alternador - Herrera De La Cruz, Jorge Ismael (2019)
The present project has begun with the mentality that Ecuador has become a country with great automobile affluence, starting from this point it is taken into account Cotopaxi province as the union between the Costa, Sierra and the Amazon region, the number of vehicles circulating on the Panamericana’s Highway has increased abruptly in the last decade, which leads us to look for adequate maintenance for cars, which is reliable and at the same time of prompt action. Much of the damage to a vehicle is generated in the electrical system, which highlights three essential elements: the alternator (generator), the battery and the connection cables, the alternator is the element with the highest failure probability because they have fixed mobile and electronic elements inside them, and it is active continuously while the vehicle is on. The maintenance carried out at technical points, developed by unreliable or artisanal methods, the alternator and the maintenance team could be on risk, but also the lack of technology or the misuse of it, make these tests tend to lengthen.This is the reason to create a test bench for alternators, that allows the verification of their nominal values before being mounted again in their work place thus streamlining the maintenance performed and the reliability of the process.